A Patient with speechlessness and rhabdomyolysis: a rare presentation of severe hypocalcaemia. Issue 12 (13th December 2020) - Jiwa, Florine Helene; van den Hoek, Kim; van Zeijl, Clementine Jaantje Joanna; Kooter, Albertus Jozef
Abstract : A 29-year-old man with no medical history presented to our emergency department with episodes of sudden speechlessness, hoarseness, vomiting after drinking cold water and spasms of his hands. Chvostek's and Trousseau's signs were both seen at presentation. Blood tests revealed severe hypocalcaemia (1.03 mmol/L) and rhabdomyolysis (creatine kinase (CK) of 2962 IU/L). The patient was treated immediately with calcium intravenously with an almost immediate improvement of his voice and quick normalisation of his CK. Additional investigation showed primary hypoparathyroidism in the presence of a vitamin D deficiency, requiring lifelong treatment with calcium supplements and alphacalcidol. Severe hypocalcaemia can be life threatening and prompt treatment is essential. This case reports the unusual first presentation of hypocalcaemia via speechlessness and vomiting together with rhabdomyolysis. Identifying an atypical presentation of hypocalcaemia is critical, for it can be lifesaving.